Effect of Particle Size of Waste Glass on Mechanical Properties of Concrete - Hassan Juma Abd; Riyadh Ibrahim Atiyah; Abdaljaleel Mohammed Hashim (Journal of Madenat Alelem University College, 2019)
Three groups of concrete containing waste glass of various particles sizes were prepared, Group A (19- 4.75) mm, Group B (4.75- 0.15) mm, and Group C (< 75) µm. The waste glass was used to replace coarse aggregate in one group and fine aggregate in two groups in proportions of (10%, 20%, 30%, and 40%) by weight.   All the mixtures were proportioned with a constant water to cement ratio (w/c) of 0.4 by weight, In this research the specimens were investigated to specify the effects of the particles sizes of waste glass and the content of waste glass on compressive strength, flexural strength, and water absorption at (7 and 14) days of immersion, compared with ordinary specimen. The experimental results showed that the compressive strength and flexural strength increased with the increase of waste glass content up to 30%, and the maximum values were with particles sizes (< 75) µm, at (14) days. While the water absorption was decreased with increased of waste glass content and decreasing the particles sizes, and the minimum values were with particles sizes (< 75) µm, at ( 14) days. Therefore, the addition of waste glass was improved the mechanical properties of concrete.